Myometrial physiology – time to translate?. Issue 3 (6th January 2014) - Arrowsmith, Sarah; Kendrick, Annabelle; Hanley, Jacqui‐Ann; Noble, Karen; Wray, Susan
<x xml:space="preserve">Abstract</x> New Findings What is the topic of this review? To provide an overview of the current understanding of myometrial contractility and give examples of where this has or is close to being applied clinically. What advances does it highlight? Examples of where myometrial science has been translated into clinical practice/patient benefit are discussed, as well as including suggestions of how it can be advanced. In this short review, we discuss how recent insights into myometrial physiology may be taken forward and translated into much‐needed novel therapies for problems associated with labour. We consider excitation–contraction coupling in the myometrium and how this relates to our understanding of the changes that occur to produce myometrial contractions and successful labour. We then discuss how this information has already been used in the development of drugs to either stimulate or relax the myometrium, to address the needs of women with either slow (dystocic) labours or threatened preterm labours, respectively. We next present the data showing how basic physiological findings pertaining to hypoxia and lactate production have been taken and translated into a tool for predicting and thus better managing difficult labours. We then highlight examples of where physiological research has started to provide mechanistic insight into clinical problems associated with labour and parturition (obesity, diabetes, advanced maternal age, postdate and twin pregnancies) and suggest how these findings could be translated into new therapies for difficult labours.